VHL protein expression in renal cell carcinoma - Rita Yadav; Mala Sagar; Malti Kumari; Atin Singhai; Suresh Babu; Ashutosh Kumar (International Journal of Medical Research and Review, 2016)
Introduction: Various studies have been performed to detect VHL gene mutation in renal cell carcinoma (RCCs) but there is paucity of literature analyzing VHL expression at the protein level. Present study was carried out to analyze VHL protein (pVHL) expression in the tissue of RCCs and its correlation with tumor grade & stage.Material and methods: Immunohistochemical detection of pVHL was done by using a mouse monoclonal antibody raised against amino acids 54-213 of VHL of human. Statistical analysis was done by using chi-square test and Kruskall Wallis H Test.Results: 32 patients of renal cell carcinoma were included in the study. pVHL expression was positive in 84.40% cases . Among all pVHL positive cases, combined cytoplasmic and nuclear expression of pVHL was most common (59.0%). Exclusive nuclear expression alone was rare and was noted in only one case. Chromophobe RCC (1 case) was negative for p VHL. Exclusive cytoplasmic pVHL expression was more frequently noticed in low grade tumors.Conclusion: VHL protein expression and its cytoplasmic and nuclear distribution is of potential relevance for the diagnosis and biological behavior of RCCs. Combined nuclear and cytoplasmic expression of VHL protein is more frequently seen in low grade and early stage of renal cell carcinomas.